HUBUNGAN SIKAP, MOTIF, MINAT DENGAN PERSEPSI SISWA SMKN 1 BENER MERIAH TENTANG GAMBAR PERINGATAN KESEHATAN MEROKOK MEMBUNUHMU - Khana Astina; Muzaffar; Andi Pratama Putra (Jurnal Ilmiah Cerebral Medika, 2026)
ABSTRACT Introduction: smoking is one of the causes of several diseases that can lead to a large number of premature deaths. Non-smoking legislation is an effective strategy to reduce smoking in adolescents with tobacco control policy objectives are to reduce the initiation and frequency of adolescent smoking, as well as encourage adolescents to stop smoking. Research methods: is a quantitative research that uses analytical research design with approach (Cross Sectional Study) and data collection is done simultaneously using questionnaires. The population of 320 students and the sample in this study amounted to 76 people, the independent variables of this study (attitudes, motives, interests of students of SMKN I Bener Meriah) and the dependent variable (perception of students of SMKN 1 Bener Meriah about health warning images smoking kills you). Results: the results obtained significant value of 0.001<0.05. So, Ha was accepted and Ho was rejected. It can be concluded that there is a significant relationship between attitudes and perceptions of SMKN 1 Bukit students about health warning images smoking kills you. Based on Chi-Square test results obtained a significant value of 0.017<0.05. So, Ha was accepted and Ho was rejected. It can be concluded that there is a significant relationship between motives and perceptions of SMKN 1 Bukit students about smoking kills you. Based on The Chi-Square test results obtained significant values of 0.000<0.05. So, Ha was accepted and Ho was rejected. It can be concluded that there is a significant relationship between interest and perception of SMKN 1 Bukit students about the health warning picture smoking kills you. Conclusions and suggestions: it can be concluded that there is a significant relationship between attitudes, motives of interest with the perception of students SMKN 1 Bener Meriah about health warning pictures smoking kills you. Suggestion: suggestions for schools to be able to put pictures of health warnings in the school environment as a warning to students against health problems. Keywords : Attitude, Motive, Interest, Perception, Health